Molecular mechanisms underlying pimaric acid-induced modulation of voltage-gated K+ channels - Kazuho Sakamoto; Yoshiaki Suzuki; Hisao Yamamura; Susumu Ohya; Katsuhiko Muraki; Yuji Imaizumi (Elsevier, 2017)
Voltage-gated K+ (KV) channels, which control firing and shape of action potentials in excitable cells, are supposed to be potential therapeutic targets in many types of diseases. Pimaric acid (PiMA) is a unique opener of large conductance Ca2+-activated K+ channel. Here, we report that PiMA modulates recombinant rodent KV channel activity. The enhancement was significant at low potentials (<0 mV) but not at more positive potentials. Application of PiMA significantly shifted the voltage-activation relationships (V1/2) of rodent KV1.1, 1.2, 1.3, 1.4, 1.6 and 2.1 channels (KV1.1-KV2.1) but KV4.3 to lower potentials and prolonged their half-decay times of the deactivation (T1/2D). The amino acid sequence which is responsible for the difference in response to PiMA was examined between KV1.1-KV2.1 and KV4.3 by site-directed mutagenesis of residues in S5 and S6 segments of Kv1.1. The point mutation of Phe332 into Tyr mimics the effects of PiMA on V1/2 and T1/2D and also abolished the further change by addition of PiMA. The results indicate that PiMA enhances voltage sensitivity of KV1.1-KV2.1 channels and suggest that the lipophilic residues including Phe332 in S5 of KV1.1-KV2.1 channels may be critical for the effects of PiMA, providing beneficial information for drug development of KV channel openers.